Toward Improving Caenorhabditis elegans Phenome Mapping With an ORFeome-Based RNAi Library - Rual, Jean-François; Ceron, Julian; Koreth, John; Hao, Tong; Nicot, Anne-Sophie; Hirozane-Kishikawa, Tomoko; Vandenhaute, Jean; Orkin, Stuart H.; Hill, David E.; van den Heuvel, Sander; Vidal, Marc (Genome Research, 2004)
The recently completed Caenorhabditis elegans genome sequence allows application of high-throughput (HT) approaches for phenotypic analyses using RNA interference (RNAi). As large phenotypic data sets become available, “phenoclustering” strategies can be used to begin understanding the complex molecular networks involved in development and other biological processes. The current HT-RNAi resources represent a great asset for phenotypic profiling but are limited by lack of flexibility. For instance, existing resources do not take advantage of the latest improvements in RNAi technology, such as inducible hairpin RNAi. Here we show that a C. elegans ORFeome resource, generated with the Gateway cloning system, can be used as a starting point to generate alternative HT-RNAi resources with enhanced flexibility. The versatility inherent to the Gateway system suggests that additional HT-RNAi libraries can now be readily generated to perform gene knockdowns under various conditions, increasing the possibilities for phenome mapping in C. elegans.
10.1101/gr.2505604